Endovascular Treatment of Very Small and Very Large Ruptured Aneurysms of the Anterior Cerebral Circulation: A Single-Center Experience - Mohammadian, Reza; Asgari, Mohamad; Sattarnezhad, Neda; Mansourizadeh, Reza; Mohammadian, Farideh; Shimia, Mohammad; Talebi, Mahnaz; Meshkini, Ali; Amirkolahy, Morteza (Cerebrovascular diseases (Basel, Switzerland), 2013)
Introduction: Endovascular treatment of aneurysms has been introduced as a less invasive method for decreasing the rate of aneurysm rerupture and subsequent subarachnoid hemorrhage. The outcome and complication rate for endovascular treatment of very small (≤3 mm) and very large (15-25 mm) intracranial aneurysms has been controversial. Here we report our experience with endovascular coiling of very small and very large ruptured aneurysms of the anterior cerebral circulation. Methods: Patients were included in the study if the maximum dimension of the intracranial ruptured aneurysm was reported to be ≤3 mm or 15-25 mm and if the aneurysm was within the anterior cerebral circulation. The largest dimension was calculated using CT angiography and was confirmed by digital subtraction angiography. Endovascular coiling was performed using Guglielmi detachable coils. All patients underwent follow-up contrast MR angiography every 6 months. Results: A total of 40 cases (18 females and 22 males) were included in this single-center study. Twenty-one very small and 19 very large ruptured aneurysms were analyzed. Preprocedural Hunt and Hess grades were determined. Endovascular coiling was performed successfully in most cases (97.5%), with unsuccessful coiling in 1 patient with a very small ruptured aneurysm. In the very small aneurysm group, the most common location was the anterior communicating artery and, in the large aneurysm group, the most common location was the middle cerebral artery (MCA) bifurcation. The mean follow-up time was 15.08 months (range: 6-30 months). The 6th month modified Rankin scale (mRS) values for very small aneurysm cases were 0 (no symptoms at all) in 16 cases (76.2%) and 1 (no significant disability despite symptoms) in 5 cases (23.80%). For the very large aneurysm cases, the mRS values were 1 in 2 cases (10.5%), 2 in 7 cases (36.8%), 3 in 6 cases (31.6%), 4 in 3 cases (15.8%) and 6 in 1 case (died due to vasospasm 72 h later; 5.2%). The immediate complications that were observed were MCA branch occlusion in 1 very small aneurysm patient and early vasospasms in 3 very large aneurysm patients. The late complication that was observed was recanalization in 1 very small aneurysm case (1/21, 4.76%) and in 5 very large aneurysm cases (5/18, 27.77%). Conclusion: Endovascular treatment of very small aneurysms is an effective method of treatment with acceptable immediate and long-term outcomes. Immediate and long-term complications were more prevalent in very large ruptured aneurysms.